Electrochemical studies of carbon nanotube-reduced graphene oxide wrapped iron cobaltite for all-solid-state asymmetric supercapacitor / Akmal Arsyad Mohd Raffi - Mohd Raffi, Akmal Arsyad (2024)
Supercapacitors employing transition metal oxide electrodes exhibit larger specific capacitances and energy densities. However, transition metal oxides have smaller surface area, which limit the kinetic in redox reaction. Performance enhancement of the transition metal oxide electrodes can be achieved by incorporation of carbonaceous materials, to form composite electrode. However, incorporation of carbonaceous materials during the synthesis process can alter the morphology properties of the transition metal oxides. Iron cobaltite, FeCo2O4 with nanosheets morphology (FCO) was synthesized by hydrothermal method. It exhibits large specific surface area and pore volume, which enhances the loading and diffusion of ions within the electrode. Herein, we designed composite electrodes made up of FCO, reduced graphene oxide (rGO) and functionalized multi-walled carbon nanotubes (f-MWCNTs) while retaining the high specific surface area of the FCO nanosheets. The composite electrodes were prepared by a two-step hydrothermal process. The prepared composite electrodes were characterized for their structural, morphological, and electrochemical properties. The composite electrodes maintained the flower-like nanosheet structure of the pristine FCO. The electrochemical properties of FCO and its composites were examined by cyclic voltammetry (CV), galvanostatic charge discharge (GCD), and electrochemical impedance spectroscopy (EIS). At 3 A g-1, the composite electrode exhibits specific capacitance, Csp of 1797 F g-1 as compared with 943 F g-1 of the pristine FCO. The higher Csp of composites as compared to FCO is because high conductive f-MWCNT and rGO help in reducing the internal resistance of the electrode. However, excessive loading of f-MWCNT and rGO bring adverse effect to the Csp performance. This is because when f-MWCNT and rGO are in excess, the porous structure of FCO can be further closed up, which is supported by the Barrett-Joyner-Halenda (BJH) analysis. Used in an asymmetric supercapacitor, the composite electrode demonstrates maximum energy density of 34 Wh kg-1, maximum power density of 4479 W kg-1 and 92 % rate capability after 5000 cycles. In contrast, the pristine FCO retains only 70 % capacitance after 3000 cycles. The performance of supercapacitors in this work is comparable with other published works.